Computer Games Addiction and Class Performance of Selected Philippine Senior High School Students - Farillon, Leah Mae Fancubila; Farillon, Kathleen Seth Fancubila; Farillon, Eulalia Fancubila (Utamax : Journal of Ultimate Research and Trends in Education, 2022)
This study was conducted to determine the relationship of computer games addiction, and class performance of Adventist Academy Iloilo Senior High School students in online classes enrolled in School Year 2021-2022. The study employed a descriptive-correlational analysis utilizing 16 student-respondents by answering a researchers-made Google form survey as the research instrument and measured using the following statistical tools: standard deviation, mean, and Pearson's r correlation coefficient. The inferential tests were set at 0.05 alpha level. The findings of the study showed that the level of computer games addiction of the respondents when taken as a whole is “average” and when grouped according to gender, the male is “high” and the female is “low” ; their level of class performance when taken as a whole is “average” and when grouped according to gender, the male has “average” and the female has “high” level of class performance; and a significant relationship of computer games addiction, and class performance when taken as a whole and when grouped according to gender is noted. The correlation coefficient is negative meaning that if there is a higher level of computer games addiction, there will be a lower level of class performance. This study implies that learners are encouraged to control their time spent in playing computer games since it affects their class performance. Parents and teachers are asked to form a partnership and use different strategies to help in improving the students’ class performance.